The Potential Role of Gut Microbiota in the Prevention and Treatment of Lipid Metabolism Disorders - Yan-Jun He; Chong-Ge You (International Journal of Endocrinology)
Due to changes in lifestyle, diet structure, and aging worldwide, the incidence of metabolic syndromes such as hyperlipidemia, hypertension, diabetes, and obesity is increasing. Metabolic syndrome is considered to be closely related to cardiovascular disease and severely affects human health. In recent years, researchers have revealed that the gut microbiota, through its own or interacting metabolites, has a positive role in regulating metabolic syndrome. Therefore, the gut microbiota has been a new “organ” for the treatment of metabolic syndrome. The role has not been clarified, and more research is necessary to prove the specific role of specific strains. Probiotics are also believed to regulate metabolic syndromes by regulating the gut microbiota and are expected to become a new preparation for treating metabolic syndromes. This review focuses on the regulation of lipid metabolism disorders by the gut microbiota through the effects of bile acids (BA), short-chain fatty acids (SCFAs), bile salt hydrolase (BSH), and genes such as ABCG5 and ABCG8, FXR, NPC1L, and LDL-R.